Changes in movement symmetry over the stages of the shoeing process in military working horses. (20th August 2016) - Pfau, T.; Daly, K.; Davison, J.; Bould, A.; Housby, N.; Weller, R.
Abstract : Military working horses perform a high proportion of work on road surfaces and are shod frequently to deal with high attrition rates. The authors investigate the influence of shoeing on movement symmetry as an indirect indicator of mechanical differences affecting force production between contralateral limbs. In this quantitative observational study, inertial sensor gait analysis was performed in 23 Irish sport type horses (4–21 years, 1.58–1.85 m) in full ceremonial work at the King's Troop, Royal Horse Artillery. Changes in two movement symmetry measures (SI: symmetry index; MinDiff: difference between displacement minima) for head and pelvic movement were assessed at four stages of routine shoeing: 'old shoes', 'shoes removed', 'trimmed', 'reshod'. Horses were assessed applying shoes to the front limbs (N=10), to the hindlimbs (N=10) or both (N=3). Changes in head movement symmetry between conditions were small and inconsistent. Changes in pelvic movement symmetry were small and showed significant differences between shoeing stages (SI: P=0.013, MinDiff: P=0.04) with most symmetrical pelvic movement after trimming. In military working horses with high frequency shoeing small changes in movement symmetry were measured. All significant changes involved trimming, which indicates that future studies should in particular assess changes before/after trimming and investigate longer shoeing intervals.